Variations in outcomes for women admitted to hospital in early versus active labour: an observational study - Yvette D. Miller; Ashleigh A. Armanasco; Laura McCosker; Rachel Thompson (BMC, 2020)
Abstract Background There is no available evidence for the prevalence of early labour admission to hospital or its association with rates of intervention and clinical outcomes in Australia. The objectives of this study were to: estimate the prevalence of early labour admission in one hospital in Australia; compare rates of clinical intervention, length of hospital stay and clinical outcomes for women admitted in early (< 4 cm cervical dilatation) or active (≥4 cm) labour; and determine the impact of recent recommendations to define early labour as < 5 cm on the findings. Methods We conducted a retrospective cohort study using medical record data from a random sample of 1223 women from live singleton births recorded between July 2013 and December 2015. Analyses included women who had spontaneous onset of labour at ≥37 weeks gestation whilst not a hospital inpatient, who had not scheduled a caesarean section before labour onset or delivered prior to hospital admission. Associations between timing of hospital admission in labour and clinical intervention, outcomes and hospital stay were assessed using logistic regression. Results Between 32.4% (< 4 cm) and 52.9% (< 5 cm) of eligible women (N = 697) were admitted to hospital in early labour. After adjustment for potential confounders, women admitted in early labour (< 4 cm) were more likely to have their labour augmented by oxytocin (AOR = 3.57, 95% CI 2.39-5.34), an epidural (AOR = 2.27, 95% CI 1.51-3.41), a caesarean birth (AOR = 3.50, 95% CI 2.10-5.83), more vaginal examinations (AOR = 1.73, 95% CI = 1.53-1.95), and their baby admitted to special care nursery (AOR = 1.54, 95% CI = 1.01-2.35). Defining early labour as < 5 cm cervical dilatation produced additional significant associations with artificial rupture of membranes (AOR = 1.41, 95% CI = 1.02-1.95), assisted vaginal birth (AOR = 1.96, 95% CI = 1.12-3.41) neonatal resuscitation (AOR = 1.73, 95% CI = 1.01-2.99) and longer maternal hospital stay (AOR = 1.21, 95% CI = 1.04-1.40). Conclusions Findings provide preliminary evidence that a notable proportion of labouring women are admitted in early labour and are more likely to experience several medical procedures, neonatal resuscitation and admission to special care nursery, and longer hospital stay.